ETIKA PEMBENTUKAN HARGA DAN PRAKTIK EKSPLOITATIF DALAM PEMIKIRAN AL-GHAZALI - Novika, Aulia; Waluyo, Agus (JSE: Jurnal Sharia Economica, 2026)
Price is a central element of the market mechanism that functions not only as a determinant of exchange value but also carries broad social implications. In practice, prices are often distorted by various exploitative practices, causing markets to lose their function of fairness. This article is situated within the discipline of Islamic economics and aims to analyse the ethics of price formation and practices of market exploitation in Al-Ghazali’s thought. The study employs a qualitative approach using a library research design. Data are collected through an examination of primary sources in the form of Al-Ghazali’s works, particularly Iḥyā’ ‘Ulūm al-Dīn, as well as secondary sources consisting of relevant contemporary academic journals and books. The analysis is conducted using a normative–critical approach, with principles of justice and public welfare (maslahah) serving as the main analytical framework. The findings indicate that Al-Ghazali conceives the market as a moral institution and views price as a reflection of the ethical quality of the relationship between sellers and buyers. Practices such as riba, ihtikar, tadlis, and ghaban are understood as forms of distortion of just pricing. The theoretical contribution of this article lies in its affirmation of market exploitation as a problem of price ethics rather than merely a technical economic violation. These findings provide an important normative foundation for understanding market justice from the perspective of Islamic economics. Keywords: Al-Ghazali; Ethics; Market Justice; Market Exploitation